Isolation and characterization of a T7-like lytic phage for Pseudomonas fluorescens - Sillankorva, Sanna (2008)
Background: Despite the proven relevance of Pseudomonas fluorescens as a spoilage microorganism in milk, fresh meats and refrigerated food products and the recognized potential of bacteriophages as sanitation agents, so far no phages specific for P. fluorescens isolates from dairy industry have been closely characterized in view of their lytic efficiency. Here we describe the isolation and characterization of a lytic phage capable to infect a variety of P. fluorescens strains isolated from Portuguese and United States dairy industries. Results: Several phages were isolated which showed a different host spectrum and efficiency of lysis. One of the phages, phage ϕIBB-PF7A, was studied in detail due to its efficient lysis of a wide spectrum of P. fluorescens strains and ribotypes. Phage ϕIBB-PF7A with a head diameter of about 63 nm and a tail size of about 13 × 8 nm belongs morphologically to the Podoviridae family and resembles a typical T7-like phage, as analyzed by transmission electron microscopy (TEM). The phage growth cycle with a detected latent period of 15 min, an eclipse period of 10 min, a burst size of 153 plaque forming units per infected cell, its genome size of approximately 42 kbp, and the size and N-terminal sequence of one of the protein bands, which gave similarity to the major capsid protein 10A, are consistent with this classification. Conclusion: The isolated T7-like phage, phage ϕIBB-PF7A, is fast and efficient in lysing different P. fluorescens strains and may be a good candidate to be used as a sanitation agent to control the prevalence of spoilage causing P. fluorescens strains in dairy and food related environments.